PENERAPAN PENGUKURAN KINERJA BERDASARKAN BALANCED SCORECARD PADA PT KAI DAOP VIII SURABAYA - Riyoko, Mas Enggar; Priyadi, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
The purpose of this research is to find out the performance of PT KAI Daop VIII which is measured by usingbalanced scorecard method. The method of research which has been done by using qualitative method which isexplained by using descriptive way to find out and to analyze the performance measurement. Four perspectiveswhich are used to measure the strategy of the company are: financial perspective is done by increasing revenuethrough maximizing the utilization of capacity in accordance with the expected target; customer perspective isdone by enhancing customer satisfaction and providing qualified services and company operational activitycontinuously and maintaining and keep on increasing the existing service quality; internal business perspectiveis done by enhancing the existing service process and innovation process that already exist in the company; andgrowth and learning perspective is done by improving the quality of employees performance in serving theservice user, the company provides training program and employees motivation to enhance the productivity ofthe employees. Based on the result of the analysis, it can be concluded that the performance measurement whichhas been done by using balanced scorecard method shows that four perspectives with the result which is inaccordance with the target company can improve the performance of service quality of the company.Keywords: Balanced Scoecard, Strategy, and Performance Measurement